Positive electrode composite material and preparation method thereof, positive electrode plate and battery

By introducing hydrophobic groups into the ternary material, the poor electrochemical stability caused by the inconsistent sensitivity of LMFP materials and NCM materials to moisture are solved, and the electrochemical stability and battery performance of the positive electrode composite material are improved.

CN119447230AActive Publication Date: 2025-02-14EVE POWER CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411490271.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

When LMFP materials are mixed with NCM materials, due to inconsistent sensitivity to moisture, the electrochemical stability is poor, which affects the circulation and storage performance of the battery.

Method used

The hydrophobic groups are introduced into the ternary material to form the first positive electrode active material so that it is consistent with the sensitivity of the second positive electrode active material to moisture, thereby maintaining the same chemical activity.

Benefits of technology

The electrochemical stability of the positive electrode composite material is improved and the circulation and storage performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447230A_ABST
    Figure CN119447230A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode composite material and a preparation method thereof, a positive electrode plate and a battery, the positive electrode composite material comprises a first positive electrode active material and a second positive electrode active material, the first positive electrode active material comprises a ternary material and a hydrophobic group, and the hydrophobic group is connected with the ternary material through a chemical bond; in the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.05. The hydrophobic group is introduced into the ternary material, so that the technical problem of relatively poor electrochemical stability caused by relatively large sensitivity difference of different positive electrode active materials in the positive electrode composite material to moisture can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode composite material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] In recent years, with the rapid development of new energy technologies, the research and development of power batteries is in full swing, and the research and development focus of power batteries has gradually focused on the development of high energy density battery materials. The new material composed of lithium manganese iron phosphate (LMFP) and ternary (NCM) materials can further improve the energy density, and the two complement each other. On the one hand, NCM materials can improve the defect of insufficient intrinsic conductivity of LMFP materials, and on the other hand, the introduction of LMFP materials can improve the thermal stability of NCM materials. Therefore, the material composed of LMFP materials and NCM materials has become an emerging lithium-ion battery positive electrode material with great market prospects.

[0003] Since LMFP and NCM materials have different sensitivity to moisture, the requirements for moisture when these two materials are used alone are different. However, when LMFP and NCM are mixed, the different moisture sensitivities will lead to poor consistency between LMFP and NCM, thus affecting the electrochemical stability of the composite material, and further affecting the battery's cycle, storage and other performance. Summary of the invention

[0004] The embodiments of the present invention provide a positive electrode composite material and a preparation method thereof, a positive electrode plate and a battery, which can improve the technical problem of poor electrochemical stability caused by large differences in the sensitivity of different positive electrode active materials to moisture in the positive electrode composite material.

[0005] In a first aspect, an embodiment of the present invention provides a positive electrode composite material, comprising a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material comprises a ternary material and a hydrophobic group, and the hydrophobic group is connected to the ternary material through a chemical bond;

[0006] Wherein, under the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.05.

[0007] In some embodiments, the hydrophobic group comprises at least one of a hydrocarbon group, a fatty acid group, an aromatic group, and a halogenated hydrocarbon group.

[0008] In some embodiments, the hydrophobic group is selected from an oleic acid group.

[0009] In some embodiments, the mass fraction of the hydrophobic group in the first positive electrode active material is in the range of 0.5% to 5%.

[0010] In some embodiments, the positive electrode composite material also includes a conductive agent and a binder; in the positive electrode composite material, the sum of the mass fractions of the first positive electrode active material and the second positive electrode active material ranges from 94.5% to 97%, the mass fraction of the conductive agent ranges from 1.5% to 3%, and the mass fraction of the binder ranges from 1.5% to 2.5%.

[0011] In some embodiments, the ternary material includes a nickel-cobalt-manganese material, and the second positive electrode active material includes a lithium manganese iron phosphate material.

[0012] In a second aspect, an embodiment of the present invention provides a method for preparing a positive electrode composite material, comprising:

[0013] forming a hydrophobic group on the ternary material to obtain a first positive electrode active material, wherein the hydrophobic group is connected to the ternary material through a chemical bond; and

[0014] At least the first positive electrode active material and the second positive electrode active material are mixed to obtain a positive electrode composite material; wherein, under the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.05.

[0015] In some embodiments, the step of forming a hydrophobic group on the ternary material to obtain a first positive electrode active material comprises:

[0016] A nickel source, a cobalt source and a manganese source are mixed and dissolved in a preset ratio to obtain a mixed salt solution, a precipitant is added to the mixed salt solution, and the solution is stirred evenly at a first preset temperature. During the stirring process, a complexing agent is added to the mixed solution, and the solution is washed and decontaminated after standing to obtain a ternary material precursor; wherein at least one of the nickel source, the cobalt source and the manganese source is connected to a hydrophobic group by a chemical bond; and

[0017] Drying the ternary material precursor at a second preset temperature, and then calcining it at a third preset temperature to obtain the first positive electrode active material;

[0018] Wherein, the nickel source is selected from nickel oleate, the cobalt source is selected from cobalt nitrate, and the manganese source is selected from cobalt sulfate; the mass fraction of the nickel source ranges from 50% to 80%, the mass fraction of the cobalt source ranges from 10% to 20%, and the mass fraction of the manganese source ranges from 10% to 30%.

[0019] In a third aspect, an embodiment of the present invention provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active layer located on at least one side of the positive electrode collector, wherein the material of the positive electrode active layer comprises the positive electrode composite material described above.

[0020] In a fourth aspect, an embodiment of the present invention provides a battery, comprising the positive electrode plate described above.

[0021] The embodiments of the present invention provide a positive electrode composite material and a preparation method thereof, a positive electrode pole piece and a battery. By introducing a hydrophobic group into a ternary material, a first positive electrode active material is obtained, so that the sensitivity of the first positive electrode active material and the second positive electrode active material to moisture tends to be consistent, so that the chemical activity of the first positive electrode active material and the second positive electrode active material in the same environment is consistent, and the electrochemical stability of the positive electrode composite material can be improved. When the positive electrode composite material is applied to the positive electrode pole piece of a battery, the cycle, storage and other performances of the battery cell can be improved. Therefore, the present application can improve the technical problem of poor electrochemical stability caused by the large difference in sensitivity of different positive electrode active materials to moisture in the positive electrode composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 is a flow chart of a method for preparing a positive electrode composite material provided by an embodiment of the present invention;

[0024] Figure 2 is a schematic structural diagram of a positive electrode sheet provided by an embodiment of the present invention;

[0025] Figure 3 is a schematic structural diagram of another positive electrode sheet provided by an embodiment of the present invention;

[0026] Figure 4 It is a schematic diagram of the structure of a battery provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the drawings; while "inside" and "outside" refer to the outline of the device.

[0028] Since the layered structure of NCM materials is more sensitive to moisture than LMFP materials, it is more likely to undergo chemical reactions after contact with moisture. For example, the material reacts with water to produce substances such as hydroxides, which affects the performance of the material and the electrochemical performance of the battery, which may lead to battery capacity decay and reduced cycle life. In addition, for high-nickel NCM materials, high nickel content is more prone to safety risks such as thermal runaway. The LMFP material has an olivine structure, which is relatively stable and less sensitive to moisture than the NCM material. Therefore, the thermal stability of the material formed by the composite of NCM material and LMFP material can be improved.

[0029] However, due to the different sensitivity of NCM materials and LMFP materials to moisture, the extent of side reactions of the two materials will be different in the same environment; when the composite material of NCM material and LMFP material is used for a long time, the deviation between the chemical activities of the two materials will become larger and larger, resulting in the electrochemical stability of the composite material becoming worse and worse, that is, the composite advantage is lost.

[0030] In order to solve the above technical problems, the present application provides a positive electrode composite material and a preparation method thereof, a positive electrode plate and a battery, and specific reference is made to the description of the following embodiments.

[0031] An embodiment of the present application provides a positive electrode composite material, which includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material includes a ternary material and a hydrophobic group, and the hydrophobic group is connected to the ternary material through a chemical bond.

[0032] Wherein, under the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.05.

[0033] In some embodiments, the sensitivity of a substance to water can be evaluated by a weight change method. Specifically, the weight change of a substance under different humidity environments is measured to determine its sensitivity to water. When a substance is exposed to an environment containing a certain amount of water, it absorbs or adsorbs water, resulting in an increase in weight. By monitoring the change in weight, the absorption capacity and sensitivity of the substance to water can be evaluated.

[0034] In some embodiments, the method for determining the weight change rate includes the following steps.

[0035] (1) Dry the substance to be tested to constant weight at a certain temperature to remove any moisture that may be contained in it and ensure the consistency of the initial state.

[0036] (2) Set different humidity environments: Use humidity control equipment, such as a constant temperature and humidity chamber, to set different relative humidity levels, such as 10%, 30%, 50%, 70%, etc.

[0037] (3) Placing samples and weighing them: Place the dried samples in different humidity environments. After a certain period of time (such as 24 hours or 48 hours), take out the samples and weigh them quickly, and record the weight of the samples under each humidity condition.

[0038] (4) Calculation of weight change rate: Calculate the weight change rate based on the weight change of the sample under different humidity conditions. Weight change rate = (weight after moisture absorption - initial weight) / initial weight × 100%.

[0039] It can be understood that the embodiment of the present application can use the weight change rate measurement method described above to measure the weight change rate A of the first positive electrode active material and the weight change rate B of the second positive electrode active material, and the ratio relationship (A / B) of A and B satisfies 0.95≤A / B≤1.05.

[0040] The embodiment of the present application introduces a hydrophobic group into the ternary material to obtain a first positive electrode active material, so that the first positive electrode active material and the second positive electrode active material have the same sensitivity to moisture, thereby making the chemical activity of the first positive electrode active material and the second positive electrode active material consistent in the same environment, thereby improving the electrochemical stability of the positive electrode composite material. When the positive electrode composite material is used in the positive electrode sheet of the battery, the cycle, storage and other performance of the battery cell can be improved.

[0041] In some embodiments, the hydrophobic group includes at least one of a hydrocarbon group, a fatty acid group, an aromatic group, and a halogenated hydrocarbon group, but is not limited thereto. By introducing these types of hydrophobic groups into the ternary material, the sensitivity of the first positive electrode active material to moisture can be reduced, so that the sensitivity of the first positive electrode active material to moisture and the second positive electrode active material are comparable, and will not have a negative impact on the ternary material.

[0042] In one embodiment, the hydrophobic group is selected from an oleic acid group. Of course, in other embodiments, the hydrophobic group can also be selected from other hydrophobic groups. The present embodiment takes the oleic acid group as an example for illustration.

[0043] In some embodiments, a hydrophobic group may be introduced into the raw materials of the ternary material (eg, a nickel source, a cobalt source, and a manganese source) so that the prepared ternary material contains the hydrophobic group.

[0044] In some embodiments, the hydrophobic group and the raw material of the ternary material are directly bonded by chemical bonds. For example, when the hydrophobic group is an oleic acid group, the nickel source of the ternary material can be selected from nickel oleate ((C 17 H 33 COO)2Ni), so that the nickel source has a hydrophobic group.

[0045] It can be understood that the chemical bonds described in the embodiments of the present application include but are not limited to covalent bonds.

[0046] It should be noted that the hydrophobic group in the embodiment of the present application can also be bonded to the ternary material through an intermediate connecting group.

[0047] In some embodiments, the mass fraction of the hydrophobic group in the first positive electrode active material is in the range of 0.5% to 5%. For example, the mass fraction of the hydrophobic group in the first positive electrode active material is 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. By controlling the content of the hydrophobic group in the range of 0.5% to 5%, the sensitivity of the ternary material to moisture can be reduced within a suitable range, so that the sensitivity of the first positive electrode active material and the second positive electrode active material to moisture tends to be consistent.

[0048] In some embodiments, the ternary material includes a nickel-cobalt-manganese material, and the second positive electrode active material includes a lithium iron manganese phosphate material. In this case, the ternary material is referred to as NCM, and the second positive electrode active material is referred to as LMFP.

[0049] Of course, in the embodiment of the present application, the metal elements in the ternary material are not limited to the combination of nickel, cobalt and manganese, and the metal elements in the second positive electrode active material are not limited to the combination of manganese, iron and lithium. The embodiment of the present application is only described by taking NCM and LMFP as examples.

[0050] In some embodiments, the positive electrode composite material further includes a conductive agent and a binder. In the positive electrode composite material, the sum of the mass fractions of the first positive electrode active material and the second positive electrode active material ranges from 94.5% to 97%, the mass fraction of the conductive agent ranges from 1.5% to 3%, and the mass fraction of the binder ranges from 1.5% to 2.5%.

[0051] For example, in the positive electrode composite material, the sum of the mass fractions of the first positive electrode active material and the second positive electrode active material is 94.5%, 95%, 95.5%, 96%, 96.5% or 97%; the mass fraction of the conductive agent is 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8% or 3%; the mass fraction of the binder is 1.5%, 1.8%, 2%, 2.2% or 2.5%.

[0052] In some embodiments, the positive electrode composite material further includes a solvent, and the solvent is selected from N-methyl-2-pyrrolidone (NMP for short), but is not limited thereto.

[0053] like Figure 1 As shown, the embodiment of the present application provides a method for preparing the positive electrode composite material described in the above embodiment, and the steps of the preparation method include S101 and S102.

[0054] S101: forming a hydrophobic group on the ternary material to obtain a first positive electrode active material, wherein the hydrophobic group is connected to the ternary material via a chemical bond.

[0055] Specifically, step S101 includes the following steps:

[0056] A nickel source, a cobalt source and a manganese source are mixed and dissolved in a preset ratio to obtain a mixed salt solution, a precipitant is added to the mixed salt solution, and the solution is stirred evenly at a first preset temperature; a complexing agent is slowly added dropwise to the mixed solution during the stirring process, and the solution is washed and decontaminated after standing to obtain a ternary material precursor; wherein at least one of the nickel source, the cobalt source and the manganese source is connected to a hydrophobic group by a chemical bond; and

[0057] The ternary material precursor is dried at a second preset temperature, and then calcined at a third preset temperature to obtain a first positive electrode active material.

[0058] In a specific embodiment, the nickel source is selected from nickel oleate, the cobalt source is selected from cobalt nitrate, and the manganese source is selected from cobalt sulfate. In addition, the mass fraction of the nickel source is in the range of 50% to 80%, the mass fraction of the cobalt source is in the range of 10% to 20%, the mass fraction of the manganese source is in the range of 10% to 30%, and the sum of the mass fractions of the nickel source, the cobalt source, and the manganese source is 100%.

[0059] In a specific embodiment, nickel oleate, cobalt nitrate and manganese sulfate are dissolved in deionized water according to the stoichiometric ratio of the target ternary material to prepare a mixed salt solution, and the concentration of the mixed salt solution is controlled between 0.5 mol / L and 2.0 mol / L.

[0060] For example, the concentration of the mixed salt solution is 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L or 2.0 mol / L.

[0061] In one specific embodiment, the precipitant is selected from sodium hydroxide solution, and the concentration of the sodium hydroxide solution ranges from 5 mol / L to 10 mol / L.

[0062] For example, the concentration of the sodium hydroxide solution is 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L.

[0063] In one specific embodiment, the complexing agent is selected from aqueous ammonia, and the concentration of aqueous ammonia is 2 mol / L to 6 mol / L.

[0064] For example, the concentration of the ammonia water is 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L or 6 mol / L.

[0065] In one embodiment, the first preset temperature ranges from 50°C to 90°C.

[0066] For example, the first preset temperature is 50°C, 60°C, 70°C, 80°C or 90°C.

[0067] In a specific embodiment, the second preset temperature ranges from 80°C to 120°C, and the third preset temperature ranges from 700°C to 1000°C.

[0068] For example, the second preset temperature is 80°C, 90°C, 100°C, 110°C or 120°C, and the third preset temperature is 700°C, 800°C, 900°C or 1000°C.

[0069] In one embodiment, the calcination time ranges from 5 hours to 15 hours.

[0070] For example, the calcination time is 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.

[0071] It should be noted that the ternary material in the first positive electrode active material formed by calcination has a specific crystal structure, and the obtained first positive electrode active material can also be stored after being crushed and screened.

[0072] In a specific implementation, step S101 includes the following steps:

[0073] Dissolving nickel oleate, cobalt nitrate and manganese sulfate in deionized water according to the stoichiometric ratio of the target ternary material to prepare a mixed salt solution, wherein the concentration of the mixed salt solution is controlled between 0.5 mol / L and 2.0 mol / L;

[0074] Under stirring, slowly adding a sodium hydroxide solution having a concentration ranging from 5 mol / L to 10 mol / L to the mixed salt solution, and controlling the pH value of the mixed salt solution to be between 10 and 13;

[0075] The mixed salt solution is stirred at 50° C. to 90° C. at a speed of 300 to 600 rpm, and at the same time, ammonia water with a concentration ranging from 2 mol / L to 6 mol / L is slowly added dropwise to the mixed salt solution to perform a precipitation reaction;

[0076] The solution is allowed to stand for 12 to 16 hours to promote further growth and crystallization of the precipitated particles;

[0077] The precipitate is repeatedly washed with deionized water to remove impurity ions to obtain a ternary material precursor; and

[0078] Drying the ternary material precursor at 80° C. to 120° C. to obtain a precursor powder;

[0079] The dried precursor powder is placed in a high-temperature furnace for calcination, the temperature is controlled at 700° C. to 1000° C., and the calcination time is 5 to 15 hours to form a first positive electrode active material with a specific crystal structure.

[0080] In some embodiments, the mass fraction of the hydrophobic group in the first positive electrode active material ranges from 0.5% to 5%. For example, the mass fraction of the hydrophobic group in the first positive electrode active material is 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0081] It can be understood that the content of hydrophobic groups on the ternary material can be controlled by adjusting the ratio of nickel oleate.

[0082] S102: Mix at least a first positive electrode active material and a second positive electrode active material to obtain a positive electrode composite material; wherein, under the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.05.

[0083] Specifically, the weight change rates of the first positive electrode active material and the second positive electrode active material can be obtained by the aforementioned method for measuring the weight change rate, which will not be described in detail herein.

[0084] In some embodiments, the second positive electrode active material may be selected from positive electrode active materials containing at least two metal elements of manganese, iron, and lithium.

[0085] In one embodiment, the second positive electrode active material is selected from lithium manganese iron phosphate (LMFP).

[0086] Since the ternary (NCM) material and lithium iron manganese phosphate (LMFP) material are used in combination, the energy density can be effectively improved, and the NCM material can improve the defect of insufficient intrinsic conductivity of the LMFP material, while the LMFP material can improve the thermal stability of the NCM material. Therefore, the use of the material composed of the first positive electrode active material and the second positive electrode active material to make the positive electrode sheet is conducive to improving the energy density, electrochemical stability and thermal stability of the battery, thereby improving the battery's cycle and storage performance.

[0087] Specifically, in step S102, the step of mixing at least the first positive electrode active material and the second positive electrode active material to obtain a positive electrode composite material includes the following steps:

[0088] The first positive electrode active material, the second positive electrode active material, the conductive agent and the binder are dispersed in a solvent and stirred evenly to obtain a slurry of the positive electrode composite material.

[0089] In some embodiments, the solvent is selected from NMP.

[0090] In some embodiments, in the positive electrode composite material, the sum of the mass fractions of the first positive electrode active material and the second positive electrode active material ranges from 94.5% to 97%, the mass fraction of the conductive agent ranges from 1.5% to 3%, and the mass fraction of the binder ranges from 1.5% to 2.5%.

[0091] For example, in the positive electrode composite material, the sum of the mass fractions of the first positive electrode active material and the second positive electrode active material is 94.5%, 95%, 95.5%, 96%, 96.5% or 97%; the mass fraction of the conductive agent is 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8% or 3%; the mass fraction of the binder is 1.5%, 1.8%, 2%, 2.2% or 2.5%.

[0092] In some embodiments, the positive electrode composite material slurry is coated on at least one side of the positive electrode current collector, and the positive electrode sheet can be manufactured through processes such as drying and cold pressing.

[0093] It can be understood that the positive electrode composite material provided in the embodiments of the present application can be applied to the positive electrode plate of the battery.

[0094] In the embodiment of the present application, a first positive electrode active material is obtained by introducing a hydrophobic group into the ternary material, so that the sensitivity of the first positive electrode active material and the second positive electrode active material to moisture tends to be consistent, so that the chemical activity of the first positive electrode active material and the second positive electrode active material in the same environment is consistent, thereby improving the electrochemical stability of the positive electrode composite material. When the positive electrode composite material is used in the positive electrode sheet of the battery, the cycle, storage and other performances of the battery cell can be improved.

[0095] like Figure 2 and Figure 3 As shown, the embodiment of the present application further provides a positive electrode plate 1, which includes a positive electrode collector 2 and a positive electrode active layer 3 located on at least one side of the positive electrode collector 2, and the material of the positive electrode active layer 3 includes the positive electrode composite material described in the above embodiment.

[0096] In some embodiments, the mixed slurry formed by the positive electrode composite material described in the above embodiments is coated on the surface of the positive electrode collector 2 , and dried and rolled to form the positive electrode sheet 1 .

[0097] In some embodiments, the material of the positive electrode current collector 2 may be metal, such as aluminum or copper, but is not limited thereto.

[0098] In some embodiments, the positive electrode current collector 2 may be a sheet structure having two opposite surfaces, and at least one surface of the positive electrode current collector 2 is coated with a positive electrode composite material. Figure 2 As shown, the positive electrode composite material can be coated on one surface of the positive electrode current collector 2 to form the positive electrode active layer 3, or, as shown in Figure 3 As shown, the positive electrode composite material is coated on two opposite surfaces of the positive electrode current collector 2 to form a positive electrode active layer 3 .

[0099] In some embodiments, the single-surface density of the positive electrode active layer 3 is 210 g / m 2 ~230g / m 2 When the single-sided surface density is within the above range, the battery has a good endurance. When the surface density is too low, the battery capacity is too small, resulting in insufficient endurance; when the surface density is too high, there is a problem of insufficient dynamics on the one hand, and on the other hand, it will lead to an increase in manufacturing costs.

[0100] In the embodiment of the present application, since the material of the positive electrode active layer 3 on the positive electrode plate 1 includes the aforementioned positive electrode composite material, and the first positive electrode active material and the second positive electrode active material in the positive electrode composite material are very similar in sensitivity to moisture, the chemical activity of the first positive electrode active material and the second positive electrode active material in the positive electrode active layer 3 remain consistent in the same environment, which is beneficial to improving the electrochemical stability of the positive electrode plate 1, and further can improve the cycle, storage and other performances of the battery cell using the positive electrode plate 1.

[0101] like Figure 4 As shown, an embodiment of the present application further provides a battery 4, which includes a battery housing 5 and an electrolyte (not shown in the figure) located in the battery housing 5, a negative electrode plate 6, a separator 7 and the positive electrode plate 1 described in the above embodiment.

[0102] The battery housing 5 has a receiving chamber 8, in which the negative electrode sheet 6, the separator 7 and the positive electrode sheet 1 are sequentially stacked, and the electrolyte is contained in the receiving chamber 8. The material of the battery housing 5 can be metal, such as steel, aluminum and the like.

[0103] In some embodiments, the negative electrode sheet 6 includes a negative electrode current collector and a negative electrode material coated on the negative electrode current collector, and the negative electrode material may include graphite, a conductive agent, a binder, etc. The negative electrode sheet is formed by coating a mixture slurry formed by the negative electrode material on the surface of the negative electrode current collector, drying, and rolling.

[0104] In some embodiments, the battery 4 is a lithium-ion battery, but is not limited thereto.

[0105] In some embodiments, the assembly steps of the battery 4 include: cutting, die-cutting, and striping the vacuum-dried positive electrode sheet 1, negative electrode sheet 6, and separator 7, and then injecting electrolyte under high temperature and negative pressure to assemble into a square aluminum shell battery.

[0106] The present application also provides Example 1, Comparative Example 1 and Comparative Example 2 to test the performance of the battery, and specifically tests the cycle performance of the battery. Among them, the structures of the batteries provided in Example 1, Comparative Example 1 and Comparative Example 2 are the same and are the batteries described in the above embodiments, and only the ratio relationship (A / B) of the weight change rate A of the first positive electrode active material and the weight change rate B of the second positive electrode active material in the positive electrode sheet is different.

[0107] Specifically, in the batteries provided in Example 1, Comparative Example 1 and Comparative Example 2, the first positive electrode active material in the positive electrode plate is an NCM material containing a hydrophobic group, and the second positive electrode active material in the positive electrode plate is an LMFP material.

[0108] It should be noted that the hydrophobic groups in the first positive electrode active materials in Example 1, Comparative Example 1 and Comparative Example 2 are the same hydrophobic groups, and only the contents of the hydrophobic groups are different.

[0109] Specifically, the content of the hydrophobic group in the first positive electrode active material in Example 1 is 2.7 wt %, the content of the hydrophobic group in the first positive electrode active material in Comparative Example 1 is 0.3 wt %, and the content of the hydrophobic group in the first positive electrode active material in Comparative Example 2 is 5.9 wt %.

[0110] The weight change rates of the positive electrode active materials in Example 1, Comparative Example 1 and Comparative Example 2 were measured by the weight change rate determination method described above and are shown below:

[0111] In Example 1, the weight change rate A of the NCM material containing the hydrophobic group in the positive electrode sheet is 0.35%, and the weight change rate B of the LMFP material in the positive electrode sheet is 0.36%;

[0112] In Comparative Example 1, the weight change rate A of the NCM material containing the hydrophobic group in the positive electrode sheet is 0.43%, and the weight change rate B of the LMFP material in the positive electrode sheet is 0.36%;

[0113] In Comparative Example 2, the weight change rate A of the NCM material containing the hydrophobic group in the positive electrode plate is 0.21%, and the weight change rate B of the LMFP material in the positive electrode plate is 0.36%.

[0114] The test method for cycle performance is as follows:

[0115] The batteries provided in Example 1, Comparative Example 1 and Comparative Example 2 were placed at 25°C for 1 hour, and then charged to 4.2V at 1C constant current and constant voltage, with a cut-off current of 0.05C; then placed for 30 minutes and placed at 1C constant current to 2.5V; after 500 cycles, the stability of the material was evaluated by the cycle capacity retention rate, and the test results are shown in Table 1.

[0116] Table 1

[0117] Example 1 Comparative Example 1 Comparative Example 2 A 0.35% 0.43% 0.21% B 0.36% 0.36% 0.36% Ratio relationship (A / B) 0.98 1.20 0.60 Cycle performance 93.70% 91.80% 92.60%

[0118] It can be seen from Table 1 that the ratio relationship (A / B) of the weight change rate A of the first positive electrode active material and the weight change rate B of the second positive electrode active material in Example 1 meets the requirement of 0.95≤A / B≤1.05; while the content of hydrophobic groups in the first positive electrode active material in Comparative Example 1 is too low, and the content of hydrophobic groups in the first positive electrode active material in Comparative Example 2 is too high, resulting in that the ratio relationship (A / B) of the weight change rate A of the first positive electrode active material and the weight change rate B of the second positive electrode active material in Comparative Example 1 and Comparative Example 2 do not meet the requirement of 0.95≤A / B≤1.05.

[0119] As can be seen from Table 1, when the ratio (A / B) of the weight change rate A of the first positive electrode active material (NCM material containing hydrophobic groups) and the weight change rate B of the second positive electrode active material (LMFP material) meets the requirement of 0.95≤A / B≤1.05, the battery has the best cycle performance. In addition, when the sensitivity of the NCM material to moisture is too high or too low, the cycle performance of the battery will deviate. Because no matter whether the sensitivity of the NCM material to moisture is too high or too low, in the presence of water, the NCM material will undergo partial redox reaction, resulting in changes in the crystal structure of the NCM material or the LMFP material, affecting the ability of lithium ion to be embedded and removed. When the degree of damage to the NCM material and the LMFP material due to the redox reaction is different, the embedding and removal of lithium ions will tend to the material with less damage. From the material level, one of the materials (such as LMFP material) is deeply charged and discharged, while the other material (such as NCM material) is shallowly charged and discharged; as the cycle increases, this differentiated charging and discharging phenomenon will become more obvious, resulting in the deterioration of the electrochemical stability of the material, and then the deterioration of the battery's cycle performance.

[0120] Therefore, the introduction of hydrophobic groups will increase the hydrophobicity of the material, making it more stable in a humid environment; the introduction of appropriate hydrophobic groups can improve the conductivity and stability of the material; by regulating the moisture sensitivity of NCM materials and LMFP materials to maintain a comparable level, the electrochemical stability can be improved, which is beneficial to improving the cycle performance of the battery.

[0121] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A positive electrode composite material, characterized in that: The invention comprises a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material comprises a ternary material and a hydrophobic group, and the hydrophobic group is connected to the ternary material through a chemical bond; Wherein, under the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.

05.

2. The positive electrode composite material according to claim 1, characterized in that: The hydrophobic group includes at least one of a hydrocarbon group, a fatty acid group, an aromatic group, and a halogenated hydrocarbon group.

3. The positive electrode composite material according to claim 2, characterized in that: The hydrophobic group is selected from oleic acid groups.

4. The positive electrode composite material according to claim 1, characterized in that: The mass fraction of the hydrophobic group in the first positive electrode active material is in the range of 0.5% to 5%.

5. The positive electrode composite material according to claim 1, characterized in that: The positive electrode composite material also includes a conductive agent and a binder; In the positive electrode composite material, the sum of the mass fractions of the first positive electrode active material and the second positive electrode active material ranges from 94.5% to 97%, the mass fraction of the conductive agent ranges from 1.5% to 3%, and the mass fraction of the binder ranges from 1.5% to 2.5%.

6. The positive electrode composite material according to any one of claims 1 to 5, characterized in that: The ternary material includes a nickel-cobalt-manganese material, and the second positive electrode active material includes a lithium manganese iron phosphate material.

7. A method for preparing a positive electrode composite material, characterized in that: include: forming a hydrophobic group on the ternary material to obtain a first positive electrode active material, wherein the hydrophobic group is connected to the ternary material through a chemical bond; as well as At least the first positive electrode active material and the second positive electrode active material are mixed to obtain a positive electrode composite material; wherein, under the same humidity environment, the ratio of the weight change rate of the first positive electrode active material to the weight change rate of the second positive electrode active material is greater than or equal to 0.95 and less than or equal to 1.

05.

8. The method for preparing the positive electrode composite material according to claim 7, characterized in that: The step of forming a hydrophobic group on the ternary material to obtain a first positive electrode active material comprises: A nickel source, a cobalt source and a manganese source are mixed and dissolved in a preset ratio to obtain a mixed salt solution, a precipitant is added to the mixed salt solution, and the mixed salt solution is stirred evenly at a first preset temperature. During the stirring process, a complexing agent is added to the mixed solution, and the mixed solution is washed and decontaminated after standing to obtain a ternary material precursor; wherein at least one of the nickel source, the cobalt source and the manganese source is connected to the hydrophobic group through a chemical bond; and Drying the ternary material precursor at a second preset temperature, and then calcining it at a third preset temperature to obtain the first positive electrode active material; Wherein, the nickel source is selected from nickel oleate, the cobalt source is selected from cobalt nitrate, and the manganese source is selected from cobalt sulfate; the mass fraction of the nickel source ranges from 50% to 80%, the mass fraction of the cobalt source ranges from 10% to 20%, and the mass fraction of the manganese source ranges from 10% to 30%.

9. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector, wherein the material of the positive electrode active layer comprises the positive electrode composite material according to any one of claims 1 to 6.

10. A battery, characterized in that: Comprising the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Anode material of lithium ion battery

    CN101640262A

  • Lithium ion battery electrode sheet, preparation method thereof, and lithium ion battery

    CN109167021A

  • Hydrophobic lithium battery positive electrode material, positive electrode and preparation method of positive electrode

    CN112397719A

  • Preparation method and equipment of positive electrode material precursor

    CN116253368A

  • Positive electrode for lithium secondary battery and lithium secondary battery

    JP2013058451A